Pyrolyzed Agro-Food By-Products: A Sustainable Alternative to Coal - Jeníček, Lukáš; Malaťák, Jan; Velebil, Jan; Neškudla, Michal (Materials (Basel, Switzerland), 2025)
This study investigates the potential use of biochar derived from residues-such as spruce wood, spent coffee grounds, tea waste, and nutshells-as a sustainable coal substitute-to enhance the decarbonization of European energetic systems and decrease the dependence on fossil fuels. The biomasses were pyrolyzed at 250-550 °C, analyzed for calorific value and composition, and evaluated for energy retention and mass loss. The results show significant energy density improvements, with optimal temperatures varying by material (e.g., spruce wood reached 31.56 MJ·kg-1 at 550 °C, retaining 21.84% of its mass; spent coffee grounds peaked at 31.26 MJ·kg-1 at 350 °C, retaining 37.53%). Economic analysis confirmed pyrolyzed biomass as a cost-effective alternative to coal, especially considering emission allowance costs. Integrating biomass pyrolysis into regional energy systems supports decarbonization, reduces emissions, and advances us towards a circular economy.
Keywords: biomass; energy residual; nut shells; calorific value; spruce wood; biochar; spent coffee ground; tea waste